Global climate change impacts on vector ecology and vector-borne diseases - Vieira, Rafael F.C.; Muñoz-Leal, Sebastián; Faulkner, Grace; Şuleşco, Tatiana; André, Marcos R. [UNESP]; Pesapane, Risa (Elsevier, 2023)
Climate change is incrementally resulting in the rise of global temperatures and is a major driver for global environmental modifications. It results in biodiversity loss, altered microclimates, and shifts in the burden and distribution of arthropod vectors, effectively expanding the geographic regions at risk for vector-borne diseases (VBDs). The COVID-19 pandemic has presented a different type of crisis since public health surveillance and control of vectors, as well as VBDs, eroded as public health organizations were forced to redirect a majority of their attention, workforce, and resources to quell the pandemic. The future of VBD management must involve a fully integrated, adaptive One Health approach to human, animal, plant, and environmental health. A transdisciplinary approach that includes entomologists, acarologists, ecologists, human and animal health professionals, plant pathologists, data scientists, and microbiologists across sectors that also engage regulatory bodies and communities to enhance research, identify and address gaps in knowledge, and optimize approaches to the surveillance and control is needed.
Keywords: Fleas; Mites; Mosquitoes; Pandemics; Public health surveillance; Taxonomy; Ticks; Vector-borne diseases